Lithological Mapping and Identification of Argillic and Propylitic Alteration Zones at Anjerd Volcanic Terrain (Revista Geoaraguaia, 2021)
Anjerd area is part of Arasbaran volcanic-magmatic terrain in northwestern Iran. The area is covered by multiple intrusive bodies of diverse compositions, volcanic, volcaniclastic, sedimentary and young alluvial deposits. The usefulness of Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) data for the lithologic mapping of the area and identification of alteration zones is investigated in this study. To carry out the study, one ASTER frame was atmospherically calibrated by Internal Average Relative Reflectance (IARR). The False Color Composite (FCC) and Principal Component Analysis (PCA) images were used for discriminating lithologic units along with Spectral Angle Mapper (SAM) and Matched Filtering (MF). The pure endmember image spectra were extracted from Pixel Purity (PPI) algorithm. The results showed that PCA and FCC can be used to discriminate sedimentary rocks from magmatic and volcanic rocks. Because feldspars and quartz are relatively featureless in shortwave infrared (SWIR) spectral region the methods were not capable to distinguish between various magmatic rocks except for basalts with darker color and higher pyroxene content. The MF gave better results than SAM algorithm and therefore MF is recommended over SAM for studying similar terrains. The argillic and propylitic alteration zones were detected by band ratios. The results showed that MF algorithm in combination with band ratios can be used to distinguish magmatic rocks from sedimentary rocks and delineate the alteration zones